Association Between Friedman Tongue Position and Respiratory Disturbance Index in Patients with Obstructive Sleep Apnea - Herlina, Sari Nafa; Yunika, Kanti; Suryawati, Herlina (Journal of Biomedicine and Translational Research, 2025)
Background: Obstructive sleep apnea (OSA) is characterized by repeated episodes of complete or partial upper airway obstruction during sleep. This sleep disorder is often ignored or undiagnosed because it is often underdiagnosed due to non-specific symptoms, even though it can cause health problems and interfere with the quality of life. The gold standard for diagnosing OSA is polysomnography (PSG), but PSG is not available in all healthcare facilities. The Friedman Tongue Position (FTP) examination is a simple method for estimating upper airway obstruction and is expected to serve as a screening tool for OSA risk.Objective: To determine the association between Friedman Tongue Position and the Respiratory Disturbance Index (RDI) in obstructive sleep apnea. To determine the association between body mass index, age, and sex with the respiratory disturbance index in obstructive sleep apnea.Methods: The study was conducted from August to October 2024 at Dr. Kariadi Central General Hospital Semarang, with a total sample of 44 adults (>18 years), comprising 22 OSA and 22 non-OSA subjects. This was a cross-sectional study involving patients who had undergone PSG. The RDI values were obtained from PSG results. FTP was assessed through tongue examination. Data were analyzed using the Chi-square test.Results: Chi-square analysis revealed significant associations between BMI (p = 0.013) and FTP (p < 0.001) and RDI. Meanwhile, Fisher’s Exact test for age (p=0.697) and Chi-square test for sex (p=0.203) indicated no significant association with RDI.Conclusion: FTP and BMI showed significant associations with RDI, where higher FTP grades and obesity increased the likelihood of OSA. In contrast, age and sex were not significantly associated with RDI, indicating that they do not independently influence respiratory disturbance severity.